PELATIHAN INTERNET MARKETING PADA SISWA SMK MUHAMMADIYAH 2 YOGYAKARTA - tikaridha hardiani; Esi Putri Silmina; Sri Lestari Linawati (DHARMA RAFLESIA, 2018)
Muhammadiyah 2 Yogyakarta Vocational School is located at Jl. Tukangan No.1, Tegal Panggung, Danurejan, Yogyakarta City, Special Region of Yogyakarta 55212. Muhammadiyah 2 Vocational School Yogyakarta has 3 departments. Department of network and computer engineering, accounting, and office administration. At present there are 325 students of Muhammadiyah Vocational High School 2 Yogyakarta. The latest curriculum used by Muhammadiyah 2 Yogyakarta Vocational School is the 2017 curriculum. Using this curriculum it is expected that students have creativity and entrepreneurial product expertise competencies. In order to achieve these competencies students of class X SMK obtain digital simulation and communication subjects. In this lesson students learn communication in online networks, online communication applications, virtual classes, virtual classroom learning, video presentations, video presentations for branding and marketing, visual simulations, preproduction stage visual simulation processing applications, visual stage simulation processing applications production, stage visual simulation processing applications, postproduction, digital books, digital book formats, and digital book publications. Therefore, to support students having these competencies, internet marketing or online marketing is needed. Muhammadiyah 2 Yogyakarta Vocational School has a business charity to support students' abilities in the form of computer and laptop services. The computer and laptop service services are located next to Muhammadiyah 2 Vocational School in Yogyakarta. The results of these computer and laptop service services have not been maximized due to lack of marketing (marketing). Students of Muhammadiyah 2 Yogyakarta Vocational School after graduating in large part did not continue to the undergraduate level, they chose to work immediately. But the Regional Minimum Wage for vocational school graduates is relatively low, therefore they need additional income by entrepreneurship. The existence of these problems, the authors provide solutions with internet marketing training to support the competence of the students' expertise. This training is also useful for students of Muhammadiyah 2 Yogyakarta Vocational School to supplement their income by entrepreneurship using the use of internet marketing as a promotional media. Keywords: internet marketing, promotion, entrepreneurship, marketing, online